Pengaruh Motivasi Kerja, Lingkungan Kerja, dan Kepuasan Kerja Terhadap Kinerja Pegawai pada PT. Sumber Alfaria Trijaya Tbk Cabang Balaraja Area Yusliana - Evlin Apriliani; Deden Kurniawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research aims to determine the influence of work environment work motivation and job satisfaction on employee performance at PT Sumber Alfaria Tijaya Tbk Balaraja Branch. The employee population of PT. Sumber Alfaria Tnjaya Tbk is 85 employees. Data was collected using a questionnaire with a liker scale which was processed using SPSS software. The research method used is multiple linear regression. The results of this research indicate that work motivation influences employee performance and the work environment influences employee performance. Job satisfaction influences employee performance. The results of this research are expected to improve employee performance at PT. SAT.